PENGARUH DISTRIBUTIVE JUSTICE SEBAGAI VARIABEL PEMEDIASI HUBUNGAN LEADER-MEMBER EXCHANGE ( LMX) DENGAN TURNOVER INTENTIONS - Yulianto, Harry; Iryani, Iryani (Benefit: Jurnal Manajemen dan Bisnis, 2007)
The purpose of this article is to analyze the effect of LMX to turnover intentionswith distributive justice as mediating variable in the hotel industry in Jogjakarta.This research examined the mediating role played by distributive justice in linkingLMX with turnover intentions.The results show that distributive justice had not a mediating impact on therelationships between LMX and turnover intentions, because the relationshipdistributive justice on turnover intentions shows not significant. So, distr ibutivejustice had not played a vital mediating role in the relationships between LMX andturnover intentions in the hotel industry.This research provides guidelines for managers to get better understanding ofhow to defend valuable employees, increase employees job satisfaction, decreaseemployee turnover, and make better decisions about outcomes for employees